Pseudo-dynamic analysis of a 3D tunnel face in inclined weak strata - Sheng Xu; Jing Liu; Xiao-Li Yang (Underground Space, 2023)
A new discretization technique is proposed for a three-dimensional (3D) tunnel face in weak strata with a random position in space. This method limits the angle, height, and thickness of the strata on the tunnel face. The original whole piece of soil is separated by a series of parallel planes, and two parallel planes are used as a stratum. Each radial discrete plane is separated when it passes through the strata, and the change in the soil properties of discrete points on the truncated plane is considered separately inside the strata. Considering the spatial and temporal characteristics of seismic waves, a pseudo-dynamic analysis of the tunnel face is carried out. The tunnel face active damage types under earthquake conditions are quantitatively analyzed, and the corresponding support pressure design diagrams are given for the case without weak strata. For the case containing weak strata, the presence of weak strata can have adverse effects on the face. The failure mechanism of the weak strata is given by the discretization method. For different friction angles, the presence of the weak strata changes the friction angles of the soils. For the thickness, location and angle of the weak strata, the variation in the support pressure is given in this paper. To more intuitively depict the change in the failure mechanism in the presence of weak strata, the change in the failure mechanism under different thicknesses and weaknesses of weak strata is plotted.